Bioefficacy of Three Indigenous Plant Extracts Against Callosobruchus Chinensis L. (BRUCHIDAE: COLEOPTERA) (Journal of the Asiatic Society of Bangladesh, Science, 2020)
Results of the evaluation on bioefficacy of three indigenous plant extracts for toxicity and residual effects against the pulse beetle, Callosobruchus chinensis L. (Bruchidae: Coleoptera) showed that the plant extracts had toxic and residual effects for controlling pulse beetle. Mortality and residual effects were statistically different among the plant extracts and doses applied. Neem extract showed the highest adult mortality (36.78%) whereas eucalyptus extract showed the lowest (22.75%). The order of the toxicity of three plant extracts was found as neem > custard apple > eucalyptus. Mortality was found directly proportional to the hour after treatments which increased with the progress of time. Between two solvents, acetone solvent possessed the highest toxicity (mortality 32.95%) but methanol showed the lowest toxicity (mortality 30.56%). The residual toxicity was evaluated on the basis of egg laid, adult emergence, seed infestation and weight loss caused by the insect. The highest residual toxicity was found in neem extract with acetone while the lowest in eucalyptus extract with acetone. Neem extract with acetone and custard apple extract with methanol solvent were found effective to toxic and residual effects against pulse beetle of three plant extracts applied.J. Asiat. Soc. Bangladesh, Sci. 46(1): 1-12, June 2020